2003
DOI: 10.1556/aphysiol.90.2003.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zink deficiency and supplementation on some hematologic parameters of rats performing acute swimming exercise

Abstract: The aim of the study was to investigate how zinc deficiency and supplementation effect some hematologic parameters of rats performing swimming exercise. Forty adult male Spraque-Dawley rats were divided into 4 groups, zinc deficient swimming group (Group 1, n=10, zinc supplemented swimming group (Group 2, n=10), swimming control group (Group 3, n=10), and control group (Group 4, n=10). Blood samples were taken by decapitation and analyzed for the determination of erythrocyte, hemoglobin level, hematocrit, leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
9
2
Order By: Relevance
“…When these two groups are compared, the exercising subjects had higher erythrocyte counts than the non-exercising individuals. This is consistent with previous studies conducted on humans and experimental animals (Baltaci et al, 2003;Dönmez et al, 2002;Kilic et al, 2004) where an increase of red blood cells was reported as a result of zincsupplementation. The fact that this parameter increased with exercise until exhaustion, suggests that is due to liquid loss resulting from intensified exercise.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When these two groups are compared, the exercising subjects had higher erythrocyte counts than the non-exercising individuals. This is consistent with previous studies conducted on humans and experimental animals (Baltaci et al, 2003;Dönmez et al, 2002;Kilic et al, 2004) where an increase of red blood cells was reported as a result of zincsupplementation. The fact that this parameter increased with exercise until exhaustion, suggests that is due to liquid loss resulting from intensified exercise.…”
Section: Discussionsupporting
confidence: 93%
“…The same happened for leukocyte subgroups such as neutrophils, lymphocytes, eosinophils and basophils. The increase of lymphocyte levels due to zinc-supplementation has been previously reported (Baltaci et al, 2003). Yet, another study demonstrated no change of leukocyte levels, which may be the result of different exercise and supplementation conditions (Banfi et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, several studies have found that zinc (Zn), a micronutrient involved in structural and regulatory functions in mammalian cells [15], could also be associated with erythrocytes production, hemoglobin [16], and serum testosterone levels [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…14 The exercise was a one-time (lasting 30 min) acute swimming exercise. Experimental animals were made to swim at the end of the study and before decapitation in groups of two.…”
Section: Swimming Exercisementioning
confidence: 99%